The use of Sprout as Precursor for the Production of Indole Acetic Acid by Selected Plant Growth Promoting Rhizobacteria Grown in the Fermentor (Microbiology Indonesia, 2016)
Indole-3-acetic acid (IAA) is the main member of the auxin family that controls many important physiological processes in plant. Such beneficial IAA that produced by plant growth promoting rhizobacteria (PGPR), enhances plant growth and was believed to increase the access to more nutrients in the soil. The precursor for syntetizing IAA is tryptophan, and it was also found in the sprout or other sources of protein. The aim of this study was to investigate the best bacteria and growth medium supplemented with extract of bean sprout or fish meal as the sources of precursor for the IAA production. Several bacterial isolates were screened for highest IAA production. IAA production was measured with High Performance Liquid Chromatography. All of isolates were able to produce IAA and isolates PS1 was selected for the further assay by cultivating under fermentor system. Sequencing of 16S rDNA of PS1 isolate indicated as Acinetobacter sp. The result showed that the highest IAA production during fermetation was 62,428 ppm found in under medium supplemented with mung bean sprout extracts grown in fermentor, after 24 hours incubation.